Etnobotani Keragaman Tumbuhan Pangan dan Pemanfatannya di Desa Labulia Kecamatan Jonggat Lombok Tengah - Lalu Amrullah; Affan Gaffar; Marsahip Marsahip (JURNAL KRIDATAMA SAINS DAN TEKNOLOGI, 2023)
Food is the main human need and continues to increase along with population growth. Food needs can be met from existing natural resources, especially from plants. Ethnobotany is a science that studies interactions between humans and plants, one of which is to meet food needs. The pattern of plant use by a society is closely related to their culture. So the culture of a region can determine the type of food, how it is processed and served. The use of plants is something that is inherent in the Using tribe, especially in meeting food needs. This research aims to gain knowledge about the diversity of types of food plants used by the community in Labulia Village, Jonggat District. The respondents used in this research were 28 people who were people who lived in the area. Data collection was carried out using interviews, questionnaires, random sampling and observation of food plant information including types, benefits and parts of plants used. Food plants used by the people of Labulia Village, 71 species consisting of 41 families. The research results show that the most widely used part of the plant is fruit with a percentage of 83%. This plant is used for foodKeywords: Ethnobotany, Food plant diversity, Labulia Village